IMPLEMENTASI KEBIJAKAN ASISTENSI REHABILITASI SOSIAL ANAK YATIM, PIATU DAN YATIM PIATU (YAPI) DI KOTA PEKANBARU TAHUN 2021 - Pazila, Laila; Rafi, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research is based on problems related to the realization of the distribution of financial aid for orphans which is still not on target, where ideally those who receive aid for orphans, orphans and orphans from the Ministry of Social Affairs through the Pekanbaru Abiseka Center should be orphans who really need it. help. The aim of this research is to describe policy implementation and the factors that influence the implementation of social rehabilitation assistance policies for orphans, orphans and orphans (YAPI) in Pekanbaru City in 2021. The research method used is descriptive qualitative, where the location of this research is at the Abiseka Pekanbaru Center. Then, the data collection techniques used were interviews and documentation. Meanwhile, data analysis was carried out using qualitative descriptive analysis techniques which describe data and information based on existing facts and then analyzed systematically. The results of this research show that in the implementation of the social rehabilitation assistance policy for orphans, orphans and orphans (YAPI) which includes the communication, resource, disposition and bureaucratic structure stages, the communication stage in policy implementation is the most visible aspect that still needs improvement, where Even though communication has been running, the process still has weaknesses in the data from the Ministry of Social Affairs of the Republic of Indonesia which is not relevant to the authenticity of the data sent to the Pekanbaru Abiseka Center. Then, the factors influencing the implementation of the social rehabilitation assistance policy for orphans, orphans and orphans (YAPI) in Pekanbaru City in 2021 include the limited availability of resources and the minimal participation of guardians of orphans in the process of determining the distribution of aid which has then been influencing the implementation of social rehabilitation assistance policies for Orphans, Orphans and Orphans (YAPI) in Pekanbaru City. Keywords : Implementation, Policy, Social Rehabilitation Assistance, Orphans